2021
DOI: 10.3389/fmicb.2021.729244
|View full text |Cite
|
Sign up to set email alerts
|

Sheltering Role of Well-Decayed Conifer Logs for Forest Floor Fungi in Long-Term Polluted Boreal Forests

Abstract: Coarse woody debris (CWD) provides food and shelter to a large proportion of forest biota and is considered vital for biodiversity during periods of harsh weather. However, its importance in long-term stressed ecosystems remains largely unknown. In this work, we explored the contribution of CWD to fungal diversity along the gradient of boreal forest degradation caused by 77 years of heavy industrial emissions. We analyzed the diversity and composition of fungi in 270 samples of well-decayed Picea abies and Abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 94 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…The abundance of several, specific Mortierella (and higher taxonomic ranks) indicates a major contribution of this fungal group in maintaining the "Metato" ecosystem functioning. Indeed, the presence of some species from this clade was preferentially observed in "sheltering" dead conifer wood (Mikryukov et al, 2021) while others were preferentially found as root endophytes (Summerbell, 2005), pointing out to different fundamental environmental services.…”
Section: Ectomycorrhizal Agaricomycetes and Mortierellomycetes As Pri...mentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of several, specific Mortierella (and higher taxonomic ranks) indicates a major contribution of this fungal group in maintaining the "Metato" ecosystem functioning. Indeed, the presence of some species from this clade was preferentially observed in "sheltering" dead conifer wood (Mikryukov et al, 2021) while others were preferentially found as root endophytes (Summerbell, 2005), pointing out to different fundamental environmental services.…”
Section: Ectomycorrhizal Agaricomycetes and Mortierellomycetes As Pri...mentioning
confidence: 99%
“…Mortierella is a ubiquitous group of soil saprotrophs and endophytes, and is often found as key component of conifer forests mycobiota (Allmér et al, 2006;Wagner et al, 2013;Mikryukov et al, 2021), even if its prominent role was also highlighted in other forests (Venice et al, 2021;Kalntremtziou et al, 2023). The abundance of several, specific Mortierella (and higher taxonomic ranks) indicates a major contribution of this fungal group in maintaining the "Metato" ecosystem functioning.…”
Section: Ectomycorrhizal Agaricomycetes and Mortierellomycetes As Pri...mentioning
confidence: 99%